Estimating Upwelling Location Using Satellite Image in South Java Sea 2009 ÃâÃâ 2010 - SUGI (NIM : 12911004), DANANG
AQUA Satellite which brings MODIS (Moderate Resolution Imaging Spectradiometer) sensor is one of satellite remote sensing which has capabilities to monitor Earth's surface especially its ocean surface. This satellite is developed by National Aeronatics and Space Administration (NASA) US. This final project implements ocean color data processing to analyze the spatial variability of SSTA (Sea Surface Temperature Anomaly) and its correlation with Ekman Pumping velocity to analyze the upwelling phenomenom in Java south sea. The study area of this research is on the coordinate 1050 -1160 BT dan lintang 70 Ã‚Â– 160 LS. The data used in this research is the Sea Surface Temperature (SST)from the mission of AQUA satellite that obtained from MODIS aand wind's velocity from CCMP. Observation time begins from January 2009 untill Desember 2010. The wind data from CCMP then be used to calculate the velocity of Ekman pumping. The result shows that on Eastern Monsoon, the value of Ekman pumping velocity tends to be positive with maximum value 0,12 cm/s.Upwelling phenomena occurs in southern java sea from Banyuwangi untill southern Yogyakarta on Juli-Agustus 2009 and 2010 with characteristic SSTA reaches -3 - -4 0C and the positive value of Ekman pumping velocity from 0,01 cm/s untill 0,08 cm/s.